Evaluation of in Ovo Delivery System for Plasmid DNA Vaccination - Moura, L.; Liu, M.; Vakharia, V.N. (International Journal of Poultry Science, 2007)
In ovo vaccination against Marek`s Disease Virus (MDV) is a common practice in more than 85% of broilers produced in the US. DNA vaccines represent a new tool to prevent infectious diseases in many species, including poultry. An in ovo delivery system for plasmid DNA vaccines is described in which we evaluate the route of delivery (air cell vs amniotic cavity), transfection reagent (IFA+DMSO vs polyethylenimine), dose of plasmid DNA (1 to 100 µg/egg) and the nature of humoral immune responses. A plasmid DNA (CMV-EGFP-BGH) construct expressing Enhanced Green Fluorescent Protein (EGFP) under cytomegalovirus (CMV) immediate early promoter was used to optimize the route of delivery and formulation for in ovo DNA vaccination. A plasmid expressing the hemmagglutinin-neuraminidase (HN) gene of Newcastle disease virus (pIRES-HN-EGFP) was used to evaluate five different dosages of DNA and the humoral immune responses after in ovo vaccination. Higher expression of EGFP and hatchability were obtained when 18-day-old embryos were inoculated through the amniotic cavity using a cationic lipid adjuvant containing polyethylenimine (PEI-ExGen®). Transgene expression was observed even when low amounts of plasmid DNA were used (1 µg/egg). A dose-dependent response was observed with plasmid DNA concentrations of 1, 10, 25, 60 and 100 µg/egg. Better responses were detected when embryos were inoculated with 60 µg of plasmid DNA. Detectable humoral responses were observed as measured by ELISA and isotope-ELISA assays.